Pengaruh Current Ratio (CR) dan Net Profit Margin (NPM) Terhadap Return Saham Syariah (Studi Pada Perusahaan Pertambangan Yang Terdaftar Dalam Jakarta Islamic Index Periode 2008-2012) - Gian Daruyudhasena; Leo Herlambang (Universitas Airlangga, 2014)
The purpose of this research is to investigate the significant effect of the variables current ration and net profit margin partially and simultaneously to the return of sharia stock on mining companies that were listed on Jakarta Islamic Index period 2008-2012). The approach that is used is multiple regression analysis technique with two variables current ratio and net profit margin as exogenous variable and return of stock as endogenous variable. The companies that are used for this research are Adaro Energy Tbk, Aneka Tambang Tbk,Borneo Lumbung Energi & Metal Tbk, Bumi Resource Tbk, Elnusa Tbk, Energi Mega Persada Tbk, Harum Energy Tbk, Vale Indonesia Tbk, Indo Tambangraya Megah Tbk, Tambang Batubara Bukit Asam Tbk, Timah Tbk. The data that is used is a secondary data. All data are gathered from the annual financial report of the period 2008-2012.The result is current ratio and net profit margin are insignificant neither partially nor simultaneously to the return of stock.